Study on MEV90 of 0.5% ropivacaine for US-guided caudal epidural block in anorectal surgery - Zhang, Pei; Chang, Hong; Yang, Taoran; Fu, Yalong; He, Xuemei; Li, Jun; Yang, Mingan; Wang, Rurong; Li, Xuehan (Frontiers in Medicine, 2023)
Background: The present study was designed to explore the minimum effective volume (MEV) of 0.5% ropivacaine in 90% of patients (MEV90) for ultrasound-guided caudal epidural block (CEB) in adults subjected to anorectal surgery. To reduce the incidence of complications associated with sacral blockade in anorectal surgery, expand the indications for surgical procedures and treatment, and enhance patient satisfaction, thereby laying a foundation for individualized anesthetic program development. Methods: We conducted two independent biased coin design up-and-down trials by gender. The volume of ropivacaine 0.5% administered to the first patient of male and female was 10ml and 8 ml respectively. The study was based on a biased coin design (BCD) up-and-down method (UDM), where the volume of ropivacaine administered to each patient depended on the response of the previous one. In case of failure, the volume was increased by 2ml in the next subject. Otherwise, the next subject was randomized to a volume of 2ml less with a probability of 0.11, or the same volume with a probability of 0.89. Success was defined as complete sensory and motor blockade of the perineal area 15 min after the block evidenced by the presence of a lax anal sphincter and pain-free surgery. When 45 successful caudal blocks were done in each group, the enrollment would be accomplished. Results: 50 males and 49 females scheduled for anorectal surgery received CEB successfully. The MEV90 of ropivacaine for CEB were estimated to be 12.88ml (95% CI 10.8 to 14ml) for male and 10.73ml (95% CI 9.67 to 12ml) for female. Conclusions: In conclusion, the present study documents the MEV90 of ropivacaine 0.5% required for anorectal surgery in a US-guided CEB. The MEV90 of ropivacaine 0.5% was 12.88 ml and 10.73ml of the male and female patients respectively.